2010
DOI: 10.1074/jbc.m110.112490
|View full text |Cite
|
Sign up to set email alerts
|

An Intrabody Based on a Llama Single-domain Antibody Targeting the N-terminal α-Helical Multimerization Domain of HIV-1 Rev Prevents Viral Production

Abstract: The human immunodeficiency virus, type 1 (HIV-1)-encoded Rev protein is essential for the expression of late viral mRNAs. Rev forms a large organized multimeric protein-protein complex on the Rev response element of these viral mRNA species and transports them from the nucleus to the cytoplasm, exploiting the CRM1-mediated cellular machinery. Here we report the selection of a nanobody, derived from a llama heavy-chain only antibody, that efficiently blocks the assembly of Rev multimers. The nanobody inhibits H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 56 publications
6
68
1
1
Order By: Relevance
“…Conversely, it is worth noting that NLS peptides have also been found to be masked in both cellular and viral protein contexts (85,(91)(92)(93). To our knowledge, this study is the first to directly implicate NES masking as a regulatory feature of Rev trafficking and the HIV-1 life cycle and may be relevant to previous observations from Daelemans and coworkers wherein targeted disruption of Rev multimerization caused reduced steady-state levels of Rev in the nucleolus (94,95). Interestingly, Gu et al have also provided evidence for cell-type-specific Rev NLS masking regulated by a cellular cofactor MDFIC (also known as the human I-mfa domain-containing protein or HIC) (96).…”
Section: Discussionsupporting
confidence: 55%
“…Conversely, it is worth noting that NLS peptides have also been found to be masked in both cellular and viral protein contexts (85,(91)(92)(93). To our knowledge, this study is the first to directly implicate NES masking as a regulatory feature of Rev trafficking and the HIV-1 life cycle and may be relevant to previous observations from Daelemans and coworkers wherein targeted disruption of Rev multimerization caused reduced steady-state levels of Rev in the nucleolus (94,95). Interestingly, Gu et al have also provided evidence for cell-type-specific Rev NLS masking regulated by a cellular cofactor MDFIC (also known as the human I-mfa domain-containing protein or HIC) (96).…”
Section: Discussionsupporting
confidence: 55%
“…These observations validated the selection of llama VHH domains for use as intracellular antibodies in this study and were in accordance with previous reports of VHHs as intracellular antibodies. [39][40][41][42][43][44] Mutation of 3 residues in CDR3 of LL3 was sufficient to disrupt antigen binding; this was in line with another intracellular domain antibody study where mutation of 4 residues in CDR1 was sufficient to disrupt intracellular function. 29 A number of studies have investigated the effect of intracellular antibody pI on intracellular aggregation, 45 and concluded that an overall negative charge at pH7.4 was beneficial to intracellular antibody solubility.…”
Section: Discussionsupporting
confidence: 58%
“…Было получено наноантитело Nb190, которое способно ингибировать белок-белковое взаимодействие, не только затрудняя мультимеризацию Rev, но также способствуя разборке уже существующих мультимеров. В итоге было показано, что экс-прессия Nb190 в цитоплазме способна дозоза-висимо ингибировать продукцию ВИЧ [123]. В 2007 году Управлением по контролю качества пищевых продуктов и лекарственных препара-тов США (FDA), а также Европейской комисси-ей был утвержден препарат Maraviroc (Selzentry, или Celsentri) -антагонист рецептора CCR5 -белка, способствующего проникновению ВИЧ в клетку.…”
Section: наноантитела для терапии бактериаль-ных и вирусных инфекцийunclassified